Dermoscopic hemorrhagic dots: an early predictor of response of psoriasis to biologic agents - Aimilios Lallas (Mattioli1885, 2016)
Background: Biologic agents are routinely used in the treatment of severe psoriasis. The evaluation of treatment response is mainly based on the physician’s global clinical assessment.